Ca2+-induced changes in the secondary structure of a 60 kDa phosphoinositide-specific phospholipase C from bovine brain cytosol. - Herrero, C (1988)
The purification to homogeneity of a 60 kDa phosphoinositide-specific phospholipase C from bovine brain cytosol is reported here. This enzyme exhibits the same properties, in terms of response to Ca2+, as does the cytosolic activity in a variety of cell types. We show here that Ca2+ does not appear to modulate the binding of the enzyme to the substrate, but induces dramatic changes in its secondary structure. Therefore we suggest that a decrease in the alpha-helix content of this enzyme correlates with its ability to be activated by Ca2+.